The efficacy of recombinant protein lbk39 for the diagnosis of leishmaniosis in dogs. Issue 3 (19th March 2021) - Pereira, Joyce Carvalho; Dos Santos Sousa, Pedro; De Souza, Ligia Moraes Barizon; Pasquali, Aline Kuhn Sbruzzi; Bates, Michelle; Bates, Paul; Thomaz Soccol, Vanete
Abstract: Visceral leishmaniosis is one of the most important zoonotic diseases on the planet and dogs are the main reservoir of canine visceral leishmaniosis (CVL) in endemic areas. They play an important role in human infection because in dogs the disease appears long time after infection, and they can move uncontrollably, contributing to disperse the parasite. To take the decision to treat the animals or for euthanasia, in an elimination programme, in order to reduce the parasitic load, it is necessary to diagnose correctly, having more effective tools. Our group has developed a new recombinant antigen-based kinesin-related gene of Leishmania braziliensis (Lbk39), which shows 59% amino acid identity to the L. infantum homologue. The Lbk39 gene was synthesized, inserted into the pLEXSY-sat2 vector and transfected into L. tarentolae cells by electroporation. The recombinant protein was secreted in the culture with a C-terminal histidine marker, purified, generating a product at 337.68 μ g mL −1 . A total of 152 sera from dog's endemic and non-endemic areas were used, being 78 positives and 75 negatives. The antigen Lbk39 showed 100% sensitivity and 96.1% specificity. We compared this antigen with other antigens such as total extract of the parasite, TRDPP, and our data indicate that Lbk39 has potential application in the diagnosis of CVL through antibody detection.